Digital Innovation Strategy: Performance of Coffee SMEs in Industrial Era 4.0 - hamdani, Nizar Alam (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2019)
Disruption in the industry 4.0 era encouraged SMEs to improve their business performance by creating digital innovation strategies. The purpose of this study is to analyze the effect of digital innovation strategies on the performance of Coffee SMEs in Garut, West Java. The method used was an explanatory survey method at the Coffee SMEs. Data processing and analyzing the relationship in the proposed structural model using SmartPLS 3. The results of this study reveal that the digital innovation strategy has a positive effect on the performance ofÂ  Coffee SMEs.